Case Report: A First Case of Spontaneous Coronary Artery Dissection Potentially Associated With Scuba Diving - Mahendiran, Thabo; Desgraz, Benoît; Antiochos, Panagiotis; Rubimbura, Vladimir (Frontiers in Cardiovascular Medicine, 2022)
Background Scuba diving has rarely been associated with spontaneous arterial dissection. However, all documented cases have involved the cervicocranial arteries. Case summary We report the first case of spontaneous coronary artery dissection (SCAD) potentially associated with scuba diving in a 65-year-old female with no medical history or known cardiovascular risk factors. She presented with sudden-onset chest pain during her descent whilst scuba diving on holiday. An initial ECG revealed transient ST-elevation in inferior leads, but due to normal initial blood tests, a reassuring echocardiogram, and the resolution of her symptoms, she was discharged from hospital without a clear diagnosis. During her subsequent presentation to our hospital one week later, electrocardiographic evidence of an inferior myocardial infarction (MI) was noted, with an echocardiogram revealing regional wall motion abnormalities of the left ventricular inferior wall. Coronary angiography revealed the presence of a SCAD of the posterior left ventricular artery, with cardiac magnetic resonance imaging confirming the presence of an inferior MI. As recommended in the majority of cases of SCAD, this case was managed conservatively with a favourable clinical course. Conclusion This is the first reported case of SCAD potentially associated with scuba diving. It highlights the importance of considering SCAD in patients presenting with sudden-onset chest pain during physical activity, especially in female patients (including older patients) with no cardiovascular risk factors. Furthermore, it serves as a reminder that symptoms during scuba diving are not always related to decompression illness.